No Place for Urban Art - Voutichtis, Christos; Rehm, Jonas Aaron (Street Art & Urban Creativity, 2016)
The following is an attempt to situate Urban Art within the philosophical tradition with and against Plato’s exclusion of the mimetic artist from the well-ordered city-state. It takes into account modern as well as postmodern literature on the concept of art and the city in order to rehabilitate a place for art within the city limits without sacrificing its potential to call into question any clear-cut limit the philosophical tradition has attempted to draw around the concepts of the subject, the work of art and the city itself.